2020
DOI: 10.1016/j.clinph.2020.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in monitoring self-produced speech in Parkinson’s disease

Abstract: Objective: Speech deficits are common in Parkinson's disease, and behavioural findings suggest that the deficits may be due to impaired monitoring of self-produced speech. The neural mechanisms of speech deficits are not well understood. We examined a well-documented electrophysiological correlate of speech self-monitoring in patients with Parkinson's disease and control participants. Methods:We measured evoked electroencephalographic responses to self-produced and passively heard sounds (/a/ phonemes) in age-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…For example, a recent study of 10 sessions of low-frequency rTMS over the right STG in individuals with PD showed increased activation of the SM1 and caudate nucleus during sentence reading ( Brabenec et al, 2021 ). There is evidence for dysfunctional self-monitoring of auditory feedback in PD ( Arnold et al, 2014 ; Railo et al, 2020 ). For example, N1 responses to self-produced speech were found to be less suppressed in individuals with PD compared to healthy individuals, and responses to passively heard phonemes were observed to be smaller ( Railo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of 10 sessions of low-frequency rTMS over the right STG in individuals with PD showed increased activation of the SM1 and caudate nucleus during sentence reading ( Brabenec et al, 2021 ). There is evidence for dysfunctional self-monitoring of auditory feedback in PD ( Arnold et al, 2014 ; Railo et al, 2020 ). For example, N1 responses to self-produced speech were found to be less suppressed in individuals with PD compared to healthy individuals, and responses to passively heard phonemes were observed to be smaller ( Railo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that the sequence effect may arise from pathological neural activity in cortical, subcortical and cerebellar circuitry that contribute to central drive, motor sequencing, sensorimotor integration, timing cues and updating of the motor set [1,5,7,22,[38][39][40][41][42]. Deficits in sensorimotor integration in PD are proposed to be related to irregular and bursting neuronal firing in basal ganglia, pre-motor and supplementary motor circuitry [43][44][45].…”
Section: Neural Basis Of the Sequence Effect And Potential Mechanism ...mentioning
confidence: 99%
“…Although initially thought to be a feature of more advanced stage PD, the sequence effect in speech and limb movement has been documented in very early stages of PD in drug naïve people [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…PD symptoms are of course a problematic confound when making assessments in movement-based paradigms such as the force-matching task, especially in the OFF-state, but the link between higher dopamine dose equivalent and increased sensory attenuation reinforces the connection to dopamine and its alteration in PD. In a speech task, people with PD also demonstrate reduced attenuation of auditory evoked activity 100 ms after sound onset when the participant speaks as compared to when the sound is externally produced [ 46 ].…”
Section: Sensory Attenuation and Task-relevancementioning
confidence: 99%